2016
DOI: 10.9790/2380-0908022024
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by Environment Interaction of Soybean (Glycine Max L. Merrill) For Yield and Yield Components in the Savanna

Abstract: Genotype-by-environment TGX 1904-6F, TGX 1935-3F, TGX 1440-1E and TGX 1984-22F falling into them. TGX 1448-2E and TGX 1895 appeared to be overall best genotypes combining high stability and yield though they did not fall into mega-environment could be recommended for use in breeding programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This nding suggested that the environment played a major role in the overall variance explained by the traits. Variation due to genotype was less than that due to the genotype*environment interaction, implying that differences among genotypes are the same across environments [10].…”
Section: Discussionmentioning
confidence: 95%
“…This nding suggested that the environment played a major role in the overall variance explained by the traits. Variation due to genotype was less than that due to the genotype*environment interaction, implying that differences among genotypes are the same across environments [10].…”
Section: Discussionmentioning
confidence: 95%